2021
DOI: 10.3389/fgene.2021.667610
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Analysis of ceRNA Network and Immune Infiltration in Kidney Renal Clear Cell Carcinoma

Abstract: Background: Kidney renal clear cell carcinoma (KIRC) has the highest invasion, mortality and metastasis of the renal cell carcinomas and seriously affects patient’s quality of life. However, the composition of the immune microenvironment and regulatory mechanisms at transcriptomic level such as ceRNA of KIRC are still unclear.Methods: We constructed a ceRNA network associated with KIRC by analyzing the long non-coding RNA (lncRNA), miRNA and mRNA expression data of 506 tumor tissue samples and 71 normal adjace… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…miRNA plays an important role in tumor diagnosis, prognosis, and treatment. 41,42 In our study, miR-21-5p, miR-221-3p, and miR-222-3p…”
Section: Discussionsupporting
confidence: 49%
“…miRNA plays an important role in tumor diagnosis, prognosis, and treatment. 41,42 In our study, miR-21-5p, miR-221-3p, and miR-222-3p…”
Section: Discussionsupporting
confidence: 49%
“…In recent years, with the rise of gene expression profiling chips, strengthening the core method for analyzing the tumor gene structure of OSCC patients is essential for guiding clinical treatment [ 17 ]. Other scholars have found [ 18 , 19 ] that the lncRNA-mediated complex network can regulate a large number of coding genes. At present, lncRNA and its target genes have become a hot topic in oncology research, and more and more studies have confirmed that differentially expressed lncRNA can be involved in the development and progression of OSCC [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that the lncRNA MALAT1 is overexpressed in T cell subsets but is not a critical regulator of T cells; furthermore, MALAT1 has been shown to be nonessential for Tfh-cell differentiation ( Yao et al, 2018 ). Although lncRNAs have not yet been shown to regulate Tfh-cell differentiation, relevant sequencing studies have indicated that many lncRNAs are relevant to Tfh pedigree transcription factors and cytokines ( Deng et al, 2021 ; Zhang et al, 2021 ). Therefore, the roles and specific mechanisms of lncRNAs in Tfh-cell differentiation are waiting for further study.…”
Section: Lncrnas Involved In Th9 and Tfh Cell Developmentmentioning
confidence: 99%